THE EFFECT OF CORPORATE SOCIAL RESPONSIBILITY, DEBT TO EQUITY RATIO, AND ASSET GROWTH ON STOCK PRICE VOLATILITY WITH FIRM SIZE AS A MODERATING VARIABLE IN CONSTRUCTION COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Megarini Dinda Saputri; Sri Marti Pramudena (Jurnal Indonesia Sosial Teknologi, 2025)
Stock price volatility is an important indicator for investors in assessing market risk, and it can be influenced by various internal and external factors. Previous studies on the effects of corporate social responsibility (CSR), debt to equity ratio (DER), and asset growth on stock price volatility have produced inconsistent findings, particularly when firm size is considered as a moderating variable. This study aims to analyze the influence of CSR, DER, and asset growth on stock price volatility, with firm size as a moderating variable, in construction companies listed on the Indonesia Stock Exchange. A quantitative approach was employed using secondary data from annual reports and financial statements of 15 construction companies for the 2018–2022 period. The data were analyzed using multiple linear regression with interaction terms to test the moderating effect. The results indicate that CSR and asset growth have a positive but insignificant effect on stock price volatility, while DER has a positive and significant effect. Firm size does not moderate the relationship between CSR and asset growth with stock price volatility but moderates and weakens the influence of DER. These findings suggest that, in the construction sector, leverage is a stronger driver of stock price volatility than CSR or asset growth, and that larger firms can mitigate the risk impact of high DER. The implications of this study highlight the need for effective debt management, strategic CSR implementation, and optimal asset utilization to reduce market risk and enhance investor confidence.